A study to determine maternal knowledge and breastfeeding practices in relation to hiv transmission in chibombo district - Malambo, Nakamba Angelinah (Lusaka: University of Zambia , School of Medicine, 2006)
This study sought to examine the viable breast milk alternatives for mothers who would be HIV positive in Chibombo district. Fifty pregnant mothers were selected from women attending antenatal care at four rural health centres. The study also sought to assess the maternal knowledge and breast feeding practices. The findings would aid in making adjustments in the area of infant feeding so as to prevent HIV among children.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Breastfeeding--Immunological aspects; AIDS (Disease) in infants--Prevention.; HIV-positive women--Zambia.